The origins of statehood in Kazakhstan. Methodology problems (Journal of Philosophy Culture and Political Science, 2018)
In this article the author examines the history of state formation in Kazakhstan. The sources of statehood of the nomad people are analyzed as the major scientific issue. The formation of the state organizations among Saks, Usuns, Kanguys and Hunnas are analyzed; the peculiarities of the first states and their relationship with the nomadic lifestyle are identified. The article provides an evidence of the continuity of the statehood in Kazakhstan. Key words: power, state, ruler, politics, nomads, tribes, Saks, Massagets, Sarmats, Usuns, Hunnas.